2020
DOI: 10.1007/s13300-020-00921-y
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Disease in Type 2 Diabetes Mellitus and Benefits of Sodium-Glucose Cotransporter 2 Inhibitors: A Consensus Statement

Abstract: Diabetic kidney disease (DKD) occurs in approximately 20-40% of patients with type 2 diabetes mellitus. Patients with DKD have a higher risk of cardiovascular and all-cause mortality. Angiotensin-converting enzyme inhibitors or angiotensin receptor blockers and antihyperglycemic drugs form the mainstay of DKD management and aim to restrict progression to more severe stages of DKD. Sodium-glucose cotransporter 2 inhibitors (SGLT2i) control hyperglycemia by blocking renal glucose reabsorption in addition to prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 99 publications
(174 reference statements)
0
8
0
Order By: Relevance
“…Diabetes mellitus (DM) is a chronic metabolic disease with a rising incidence rate, and its microvascular and macrovascular complications are associated with a large global burden of morbidity and mortality [1]. Diabetic kidney disease (DKD) is a serious kidney-related complication that is present in approximately 40% of patients with DM [2], and patients with DKD have an increased risk of cardiovascular events and all-cause mortality [3]. Abnormal blood glucose status leads to oxidative stress and induces the release of inflammatory mediators, resulting in glomerular lesions in DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a chronic metabolic disease with a rising incidence rate, and its microvascular and macrovascular complications are associated with a large global burden of morbidity and mortality [1]. Diabetic kidney disease (DKD) is a serious kidney-related complication that is present in approximately 40% of patients with DM [2], and patients with DKD have an increased risk of cardiovascular events and all-cause mortality [3]. Abnormal blood glucose status leads to oxidative stress and induces the release of inflammatory mediators, resulting in glomerular lesions in DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…T2DM induced changes such as impaired insulin signaling, hyperglycemia/glucotoxicity and lipotoxicity, are thought to contribute, along with hemodynamic changes, activation of the renin-angiotensin-aldosterone system (RAAS), endothelial dysfunction, inflammation and oxidative stress [6][7][8][9]. Indeed, approximately 20-40% of patients with T2D develop diabetic kidney disease, the most common cause of end stage renal failure [10].…”
Section: Introductionmentioning
confidence: 99%
“…37,38 In the past, cardiovascular outcome trials in Table 3 have demonstrated the efficacy of SGLT2i (empagliflozin [EMPA-REG OUTCOME], canagliflozin [CANVAS], and dapagliflozin [DECLARE-TIMI 58]) in slowing CKD progression and reducing hyperglycaemia in patients with type 2 diabetes mellitus (T2DM). [39][40][41][42][43][44][45][46][47][48] However, these are largely secondary outcomes, and the mean eGFR inclusion criteria was >60 ml/min/1.73m 2 . Recently, a meta-analysis study by Zhao evaluated the potential benefits of a combination of SGLT2i and ACEI/ARB over ACEI/ARB plus placebo in lowering cardiorenal events in patients with T2DM.…”
Section: Chronic Kidney Disease and Sodium-glucose Cotransporter 2 In...mentioning
confidence: 99%
“…51 Table 3: Key highlights of the SGLT2i cardiovascular outcomes trials (CVOTs). Adapted data from: Mahaffey et al 2019, 39 Wiviott et al 2019, 40 Roy et al 2020, 41 Zinman et al 2015, 42 Rangaswami et al 2020, 43 McMurray et al 2019, 44 Packer et al 2020, 45 Anker et al 2021, 46 Perkovic et al 2019, 47 Heerspink et al 2020. Table 4: A) Key highlights of CREDENCE and DAPA-CKD trials.…”
Section: Chronic Kidney Disease and Sodium-glucose Cotransporter 2 In...mentioning
confidence: 99%